PENGARUH KEPEMILIKAN SAHAM DAN FAKTOR – FAKTOR LAIN TERHADAP AGRESIVITAS PAJAK - Ericko Harsana; Meinie Susanty (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2023)
Abstract: The purpose of this study is to obtain empirical evidence related to the effect of profitability, leverage, capital intensity, independent commissioner, institutional ownership, managerial ownership, and public ownership on tax aggressiveness. The populations in this study are manufacturing companies that are consistently listed on the Indonesian Stock Exchange for 3 years from 2019 to 2021. The sample in this study used a purposive sampling method and generates 108 data from 36 sample companies. This study uses multiple regression methods in analyzing the data. The results of this study show that profitability and managerial ownership affect tax aggressiveness, while leverage, capital intensity, independent commissioners, institutional ownership, and public ownership have no effect on tax aggressiveness.